Biomechanical comparison of canine femurs implanted with either cemented (CFX®) or cementless (with lateral bolt) (BFX®+lb) total hip replacement under 4-point bending or torsional loads - Selena Tinga; David D. Tuyn; Rosalind J. Kopp; Stanley E. Kim (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Compare biomechanical properties of femurs implanted with either BioMedtrix™ biological fixation with interlocking lateral bolt (BFX®+lb) or cemented (CFX®) stems when subjected to 4-point bending or axial torsional forces.Study Design: Twelve pairs of normal medium to large cadaveric canine femora were implanted with a BFX + lb (n = 12) and a CFX (n = 12) stem–one in the right and one in the left femora of the pair. Pre- and post-operative radiographs were made. Femora were tested to failure in either 4-point bending (n = 6 pairs) or axial torsion (n = 6 pairs), and stiffness, load or torque at failure, linear or angular displacement, and fracture configuration were noted.Results: Implant position was acceptable in all included femora, but CFX stems were placed in less anteversion than BFX + lb stems in the 4-point bending group (median (range) 5.8 (−1.9–16.3) vs. 15.9 (8.4–27.9) anteversion, respectively (p = 0.04)). CFX implanted femora were more stiff than BFX + lb implanted femora in axial torsion (median (range) 2,387 (1,659–3,068) vs. 1,192 (795–2,150) N*mm/o, respectively (p = 0.03)). One of each stem type, from different pairs, did not fail in axial torsion. There was no difference in stiffness or load to failure in 4-point bending, or in fracture configuration for either test, between implant groups.Conclusion: Increased stiffness of CFX implanted femurs under axial torsional forces may not be clinically relevant as both groups withstood expected in vivo forces. Based on this acute post-operative model using isolated forces, BFX + lb stems may be a suitable replacement for CFX stems in femurs with normal morphology (stovepipe and champagne flute morphology were not tested).